«Striking force of gun turrets» — to question of creating artillery weapons of Soviet armored vehicles in 1930’s - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the development of anti-tank and tank artillery in the USSR, Belgium, Britain, Germany, Czechoslovakia, Poland, France, Italy in the Interbellum. This process is caused by the growth of the tank fleet of the armed forces, which can significantly increase the pace of operations. In parallel, there is a qualitative development of armored vehicles, which becomes more resistant to armor-piercing bullets of a rifle caliber and shell fragments, more mobile, which complicates the fight against regimental and division artillery, and makes the production of special anti-tank guns necessary. At the same time, the qualitative growth of armored vehicles requires adequate armament of a compact, rapid-fire ammunition with a wide range of ammunition. Unfortunately, the study of this process is biased. Journalists, politicians, researchers often disseminate allegations that in the USSR there was a copying of foreign samples. An example of such approaches is the distortion of the history of the development of Soviet anti-tank and tank guns of the Interbellum. A comparison of the processes taking place in the USSR and abroad allows us to refute the opinion of the fundamental importance of copying foreign samples or using pre-revolutionary experience